Adsorption of Cu(II), Zn(II), Cd(II) and Pb(II) by dead Avena fatua biomass and the effect of these metals on their growth - Areco, María del Mar (2013)
The biosorption of copper(II), zinc(II), cadmium(II) and lead(II) from aqueous solutions by dead Avenafatua biomass and the effect of these metals on the growth of this wild oat were investigated. Pseudo-first- and second-order and intra-particle diffusion models were applied to describe the kinetic data andto evaluate the rate constants. The adsorption kinetics of all the metals follows a pseudo-second-ordermodel.The adsorption capacity was determined, and the Freundlich and Langmuir models were applied. Theexperimental data obtained for all the metals are best described by the Langmuir model. A. fatua wascharacterized using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS),and zeta potential. The results obtained evidence the presence of Zn(II), Cu(II), Cd(II) or Pb(II) on thesurface of the weed.The growth of A. fatua was affected by the presence of all metals. The decrease in the growth rate withincreasing metal concentration was more noticeable for zinc.